Modelo computacional para visualizar desplazamientos atómicos en cascada de materiales sometidos a radiación ionizante (2016)
The purpose of this article is present a simplified model to visualize the displacement cascade process in the atoms of a material. This achievement can be accomplished through a computational modeling method, this method will use a computational implementation of a Lennard-Jones function and the motion equations solution through a Verlet Algorithm. As a result of the developed code, the amount of atoms displaced can be calculated from its initial position.